PENGARUH PENGGUNAAN YOUTUBE TERHADAP HASIL BELAJAR MAHASISWA - Denok Julianingsih; Evi Widayanti (Prodi Pendidikan Matematika FKIP Universitas Madura, 2021)
The purpose of this study was to determine the effect of using youtube media on student learning outcomes in the even semester 2020/2021 Statistics lectures and to see student responses while using youtube media as a source of learning information during lectures. This research is a quasi-experimental research with 18 students taking the subject of statistics. The design in this study used a one group pretest-posttest design. The instruments used in this study were a matter of learning outcomes tests and student response questionnaires. The data analysis technique used was descriptive statistical analysis and inferential statistical analysis. The data was processed using SPSS 22. Based on the results of inferential statistical analysis using the paired sample t-test, an alpha value of 0.000 <0.05 means that there is an effect of using YouTube media on student learning outcomes. It can be seen that there is a difference in the average learning outcomes before and after using YouTube, which is 54.44. In addition, based on the results of the student response questionnaire, it showed that all aspects contained in the student response questionnaire showed an average of 67.36 good results.